Mutations equivalent to Drosophila mago nashi mutants imply reduction of Magoh protein incorporation into exon junction complex. (25th April 2022) - Oshizuki, Saya; Matsumoto, Eri; Tanaka, Satoshi; Kataoka, Naoyuki
Abstract: Pre‐mRNA splicing imprints mRNAs by depositing multi‐protein complexes, termed exon junction complexes (EJCs). The EJC core consists of four proteins, eIF4AIII, MLN51, Y14 and Magoh. Magoh is a human homolog of Drosophila mago nashi protein, which is involved in oskar mRNA localization in Drosophila oocytes. Here we determined the effects of Magoh mutations equivalent to those of Drosophila mago nashi mutant proteins that cause mis‐localization of oskar mRNA. We found that Magoh I90T mutation caused mis‐localization of Magoh protein in the cytoplasm by reducing its binding activity to Y14. On the other hand, G18R mutation did not affect its binding to Y14, but this mutation reduced its association with spliced mRNAs. Our results strongly suggest that Magoh mutations equivalent to Drosophila mago nashi mutants cause improper EJC formation by reducing incorporation of Magoh into EJC.